Accident Prevention Program in the Nickel Mining Facility Project at the Indonesia Growth Project (IGP), Pomalaa - Noor Faiz Achmad; Felixtianus Eko Wismo Winarto (Rifa'Institute, 2026)
Introduction: Construction projects in nickel mining, such as the Indonesia Growth Project (IGP) Pomalaa, involve numerous workers and high-risk activities, making occupational accidents a significant concern. Safety management practices in many projects are often administrative and reactive, limiting their effectiveness in systematically preventing accidents. This study examines the implementation of accident prevention programs and identifies strategies to enhance occupational health and safety management in mining construction projects. Objective: The study aims to analyze the factors causing workplace accidents, describe how accident prevention programs are implemented, and evaluate their effectiveness in improving safety performance at the IGP Pomalaa construction project. Method: A descriptive qualitative approach was employed, complemented by secondary quantitative data. Data were collected through field observations, interviews with safety personnel including managers, officers, supervisors, and workers, as well as document reviews of safety reports, accident records, and safe work procedures. Data analysis followed the steps of reduction, presentation, and conclusion drawing to provide an in-depth understanding of the Occupational Health and Safety Management System implementation within the project. Result and Discussion: The main causes of workplace accidents were identified as Job Safety Analyses that were insufficiently specific to task hazards, unsafe worker behaviors including non-compliance with protective equipment and housekeeping procedures, weak supervision, and safety communication not fully aligned with field conditions. These factors interacted to form chains of causation consistent with accident prevention theory. The findings show that strengthening risk analysis, improving safety leadership, and implementing participatory, context-specific safety programs are critical to enhancing the safety culture in mining construction projects. Conclusions: Addressing through targeted safety programs can significantly reduce workplace accidents and improve overall safety culture in mining construction projects.